Cryptococcal meningitis in a diabetic - Jyoti Prakash; B. Anil; Tanushree Sharma (Wolters Kluwer -Medknow Publications, 2024)
A 75-year-old male, a known case of hypertension and diabetes, from Bihar, India, had presented to the medicine department with a complaint of fever for the last 1 month and drowsiness for the last 5 days. In view of drowsiness, a cerebrospinal fluid study was done which was suggestive of cryptococcosis (budding yeast in India Ink Preparation). Cryptococcal meningitis is usually found in cases of immunocompromised states like HIV and it is quite less in non-HIV patients like diabetics. Liposomal amphotericin B was started as per protocol. The patient, however, developed anuria and septic shock and succumbed to his illness. Therefore, clinicians should suspect cryptococcal meningitis in nonimmunocompromised patients also because timely treatment may be given as it has a potential cure.